2013
DOI: 10.1007/s00401-013-1130-9
|View full text |Cite
|
Sign up to set email alerts
|

Codeletion of 1p and 19q determines distinct gene methylation and expression profiles in IDH-mutated oligodendroglial tumors

Abstract: Oligodendroglial tumors (OTs) are primary brain tumors that show variable clinical and biological behavior. The 1p/19q codeletion is frequent in these tumors, indicating a better prognosis and/or treatment response. Recently, the prognostically favorable CpG island methylator phenotype (CIMP) in gliomas (G-CIMP+) was associated with mutations in the isocitrate dehydrogenase 1 and isocitrate dehydrogenase 2 (IDH) genes, as opposed to G-CIMP- tumors, highlighting the relevance of epigenetic mechanisms. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 58 publications
2
52
0
Order By: Relevance
“…Patients, samples and external datasets DNA methylation profiles through the HM-450K platform were established for 46 glioma tumor samples and five non-tumoral brain tissue (NTBT) samples used as controls [7]. Tumors included 33 samples diagnosed as OD (19 WHO grade II, 14 WHO grade III) and 13 as OA (5 WHO grade II and 8 WHO grade III).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients, samples and external datasets DNA methylation profiles through the HM-450K platform were established for 46 glioma tumor samples and five non-tumoral brain tissue (NTBT) samples used as controls [7]. Tumors included 33 samples diagnosed as OD (19 WHO grade II, 14 WHO grade III) and 13 as OA (5 WHO grade II and 8 WHO grade III).…”
Section: Methodsmentioning
confidence: 99%
“…[6,7]. On the other hand, MGMT encodes a nuclear repair enzyme (alkyltransferase) that removes O(6)-alkylating binds of guanine and helps maintain the integrity of DNA from normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of CpG methylation appears to be non-random and tumour type-specific, hence G-CIMP for glioma [52]. It has also been shown that the G-CIMP profiles are different among the IDH-mutated tumours depending on the make-up of the complete genotype, i.e., astrocytomas typically having TP53/ATRX mutations (see below) and oligodendroglioma with total 1p/19q co-deletion [92,158]. Although the targets for methylation that function as driver genes for glioma are yet to be defined [96], it is widely believed that silencing of critical gene(s) by G-CIMP is the main mechanism in the pathogenesis of IDH-mutated tumours.…”
Section: G-cimpmentioning
confidence: 96%
“…Point mutations in isocitrate dehydrogenase (IDH) 1 and 2 have been associated with improved prognosis compared to patients with wild-type IDH [10]. The combined loss of chromosomal arms 1p and 19q has been shown to occur in oligodendrogliomas and oligoastrocytomas [11], but it is associated with better response to chemotherapy and radiation therapy leading to prolonged progression-free and overall survival [12,13]. Epidermal growth factor receptor (EGFR) is a cell surface receptor involved in cell proliferation.…”
Section: Gliomasmentioning
confidence: 99%